The Naqshbandiyya-Khalidiyya, Islamic Sainthood, and Religion in Modern Times. - Foley, Sean (Journal of World History, 2008)
The article focuses on Shaykh Khalid Naqshbandi and his Sufi brotherhood, the Naqshbandiyya-Khalidiyya and Muslim sainthood. It highlights the social movement theory which allows people to see the ongoing influence of sainthood in Muslim societies. It tackles Khalid's success which resided on his ideological flexibility, appeal to multiple audiences and emphasis on the hereafter. It emphasizes that the Naqshbandiyya-Khalidiyya has addressed a desire in modern societies for a greater balance between spirituality and materialism.